Numerical simulation of iontophoresis in the drug delivery system. Issue 11 (17th August 2016) - Filipovic, Nenad; Zivanovic, Marko; Savic, Andrej; Bijelic, Goran
Abstract: The architecture and composition of stratum corneum act as barriers and limit the diffusion of most drug molecules and ions. Much effort has been made to overcome this barrier and it can be seen that iontophoresis has shown a good effect. Iontophoresis represents the application of low electrical potential to increase the transport of drugs into and across the skin or tissue. Iontophoresis is a noninvasive drug delivery system, and therefore, it is a useful alternative to drug transportation by injection. In this study, we present a numerical model and effects of electrical potential on the drug diffusion in the buccal tissue and the stratum corneum. The initial numerical results are in good comparison with experimental observation. We demonstrate that the application of an applied voltage can greatly improve the efficacy of localized drug delivery as compared to diffusion alone.